Persepsi Mahasiswa Tentang Media Pembelajaran E-Learning - Henik Istikhomah; Indarto A.S; Dewi Tustika P.S (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: According to preliminary survey in January 2014, students of DIV Midwifery Educator expressed e-learning is a great breakthrough in the learning process because it can use technology and we are able to learn everytime everywhere.Objective: Unconvering the student’s perceptions about media e-learning on educational technology adn instructional media course in Obstetrics Department at Surakarta Health PlytechnicMethods: Using a qualitative design, sample collection techniques by purposive sampling, types of sampling maximum variation sampling. Collecting data using techniques focus group discussions adn in-depth interviews. The validity of data using triangulation techniques.Result: Informans knowing e-learning is to use the internet as a learning tool. In the course of educational technology and e-learning media has begun to be used. The implementation of e-learning is not maximized due to lack of interest and technical use of the medium of e-learning. Benefits of e-learning for students, faculty and istitutions is to facilitate the learning process. Barriers to e-learning consists of interal barriers and external barriers. The disadvatage of use e-learning is no interaction between faculty adn students.Conclusion: The implementation of the e-elearning in the course of education technology and instructional media is not maximized due to lack of participation and motivation of students. Benefits of e-learning if easier for students, save costs, time flexible, enhancing the reputation of the campus. Barriers to e-learning is the lack of interest of students, the admin is not competent yet, less socialization. Disadvantages of e-learning media is the lack of interaction of faculty and students that are objective assessment only.Keyword : perception, students, the use of e-learning